The Effect of Play Therapy in Group Counseling on Junior High School Students’ Social Interaction - Dianti, Tiara Maiza; Yusra, Affan; Asradi, Asradi (Psikopedagogia, 2022)
Social interactions are dynamic relations involving individuals and groups of people. Teenagers are known to often face various problems in interaction patterns. This study aimed to find out the effect of play therapy in group counseling on students’ social interaction. To this end, a pre-experimental design was applied. Participants were ten 8th-grade students in a junior high school in Jambi, Indonesia, recruited using a purposive sampling technique. Data were collected using social interaction scale. Wilcoxon test result showed a sig. value (2-tailed) of 0.005 (<0.005), indicating that play therapy affects social interactions of students who were associative (cooperation, accommodation, assimilation) and dissociative (competition). School counselors are recommended to optimize the group counseling services with play therapy to help improve their social interaction.